2007
DOI: 10.1017/s0007114507798914
|View full text |Cite
|
Sign up to set email alerts
|

Dietary long-chainn-3 fatty acids modify blood and cardiac phospholipids and reduce protein kinase-C-δ and protein kinase-C-ε translocation

Abstract: The effects of an n-3 PUFA-enriched diet on cardiac cell membrane phospholipid fraction compositions and associated protein kinase-C (PKC) translocation modification have never been studied in higher mammals. This is of importance since membrane fatty acid composition has been shown to influence PKC signalling pathways. In the present study, we have tested whether the incorporation of n-3 PUFA in cardiac membrane phospholipids correlated with changes in the fatty acid composition of diacylglycerols (DAG) and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 38 publications
2
31
0
1
Order By: Relevance
“…A preferential incorporation of EPA was also observed in humans receiving a EPA-rich fish oil diet[32]. Our data also contradict the results of Jude et al[33] in dogs. In this study a fish oil-enriched diet containing twice as much DHA as EPA showed a preferential incorporation of EPA.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A preferential incorporation of EPA was also observed in humans receiving a EPA-rich fish oil diet[32]. Our data also contradict the results of Jude et al[33] in dogs. In this study a fish oil-enriched diet containing twice as much DHA as EPA showed a preferential incorporation of EPA.…”
Section: Discussionsupporting
confidence: 59%
“…The incorporation of n-3 FA at the expense of AA has been shown earlier by Jude et al[33] and Kew et al[26]. There was also a significant reduction of n-6 FA in FO, despite the fact, that the daily uptake of n-6 FA in this group (787.5 mg/d/kg body weight) was higher than in ADD (533.4 mg/d/kg body weight).…”
Section: Discussionmentioning
confidence: 62%
“…Since SDG and SEG in the absence or presence of SAG differentially modulated PKC isoforms, it appeared that there might be two types of binding sites for DAG species which, in the presence of PS and calcium, might signal differently. These data suggest that the actions of DAG species on PKC activation are complex and may exert both inhibitory and stimulatory effects [75, 76]. In dogs fed a fish oil diet, DAG containing n-3 PUFA were associated with a reduction in the expression of PKC-δ and PKC-ε isoforms [76].…”
Section: T-cell Activation and N-3 Pufamentioning
confidence: 99%
“…One potential explanation is that DHA inhibits sPLA 2 via ERK and PKC, as previously shown in human endothelial cells [12]. Reductions in the expression of PKC-δ and PKC-ε isoforms have also been reported in cardiomyocytes isolated from dogs fed fish oil [20]. Hence, despite an increased availability of ARA, the overall effect of DHA supplementation is conducive to lower production of inflammatory mediators.…”
Section: Discussionmentioning
confidence: 85%